Heterozygous STUB1 mutation causes familial ataxia with cognitive affective syndrome (SCA48). (20th November 2018) - Genis, David; Ortega-Cubero, Sara; San Nicolás, Hector; Corral, Jordi; Gardenyes, Josep; de Jorge, Laura; López, Eva; Campos, Berta; Lorenzo, Elena; Tonda, Raúl; Beltran, Sergi; Negre, Montserrat; et al.
Abstract : Objective: To describe a new spinocerebellar ataxia (SCA48) characterized by early cerebellar cognitive-affective syndrome (CCAS) and late-onset SCA. Methods: This is a descriptive study of a family that has been followed for more than a decade with periodic neurologic and neuropsychological examinations, MRI, brain SPECT perfusion, and genetic analysis. Whole exome sequencing was performed in 3 affected and 1 unaffected family member and subsequently validated by linkage analysis of chromosome 16p13.3. Results: Six patients fully developed cognitive-affective and complete motor cerebellar syndrome associated with vermian and hemispheric cerebellar atrophy, suggesting a continuum from a dysexecutive syndrome slowly evolving to a complete and severe CCAS with late truncal ataxia. Three presymptomatic patients showed focal cerebellar atrophy in the vermian, paravermian, and the medial part of cerebellar lobes VI and VII, suggesting that cerebellar atrophy preceded the ataxia, and that the neurodegeneration begins in cerebellar areas related to cognition and emotion, spreading later to the whole cerebellum. Among the candidate variants, only the frameshift heterozygous c.823_824delCT STUB1 (p.L275Dfs*16) pathogenic variant cosegregated with the disease. The p.L275Dfs*16 heterozygous STUB1 pathogenic variant leads to neurodegeneration and atrophy in cognition- and emotion-related cerebellar areas and reinforces the importance of STUB1 in maintaining cognitive cerebellar function. Conclusions: We report a heterozygous STUB1 pathogenic genetic variant causing dominant cerebellar ataxia. Since recessive mutations in STUB1 gene have been previously associated with SCAR16, these findings suggest a previously undescribed SCA locus (SCA48; MIM# 618093).